Antenatal care visits and its determinants among women in Afar regional state: North Eastern Ethiopia - Aragaw Asfaw Hasen (BMC Health Services Research)
Abstract Background Antenatal care is an essential component of maternal healthcare that plays a crucial role in promoting the health and well-being of both mother and baby. While previous studies have examined factors influencing antenatal care visits in other parts of Ethiopia, there is a lack of research specifically focusing on the Afar region. This study aimed to assess determinants of antenatal care visits among pregnant women in Afar region, Ethiopia. Methods The data is 2019 Ethiopian Mini Demographic and Health Survey. In this study 641 weighted sample womens were included. Negative binomial regression model is applied. Results About 27.77% achieve optimal ANC visits. Living rural (IRR = 0.575, 95%CI: 0.467, 0.708). Reading whole sentences (IRR = 1.683, 95%CI: 1.212, 2.339). Under five children in house 1–2 (IRR = 0.789, 95%CI: 0.632, 0.984), 3–4 (IRR = 0.692, 95%CI: 0.509, 0.941), > = 5 (IRR = 0.075, 95%CI: 0.021, 0.268). Married (IRR = 1.550 95%CI: 1.172, 2.051), Widowed (IRR = 2.043, 95%CI: 1.238, 3.372). Age first birth 16–20 (IRR = 0.805, 95%CI: 0.652, 0.992). Conclusion The study examined the utilization of antenatal care services among women in Afar regional state, North Eastern Ethiopia. The findings reveal that a significant proportion of women did not receive the recommended number of antenatal care visits during their pregnancy. Factors such as residence, mother’s literacy rate, age at first birth, number of living children, number of under five children in the house and marital status were major determinants of ANC (Antenatal Care) visit in Afar region. Increase access to antenatal care services by improving the availability and quality of health facilities in the region. Maternal health-care program should be expanded and mainly in rural areas of the region. Moreover, the necessary assessment and follow-up of ANC health care services should be encouraged in Afar region to decrease maternal mortality.